Ankylosing spondylitis and glaucoma in European population: A Mendelian randomization study - Li, Shengjie; Chen, Minting; Zhang, Qing; Fang, Meijin; Xiong, Wei; Bai, Lang (Frontiers in Immunology, 2023)
Background: The relationship between ankylosing spondylitis (AS) and glaucoma remains unclear. In the present study, we applied a two-sample Mendelian Randomization (MR) Method to investigate their causal relationship. Methods: MR analysis was conducted to validate the causal associations between AS with glaucoma using summary statistics from genome-wide association studies of AS (9,069 cases, 13,578 control subjects) and glaucoma (8,591 cases, 210,201 control subjects). The inverse variance weighting (IVW) method was performed to evaluate the causal relationship. The MR-egger regression approach was applied to assess pleiotropy, while the Cochran's Q test was used to analyze heterogeneity. Subgroup analysis was performed according to primary open-angle glaucoma (POAG) and primary angle closure glaucoma (PACG). Results: The results of the MR study reveal a risk-increasing causal relationship between AS and glaucoma among European populations (OR = 1.35, 95%CI = 1.16–1.57, P = 8.81 × 10-5). Pleiotropy and heterogeneity were not found in our study. In the subgroup analysis, AS was also causal with POAG (OR = 1.48, 95%CI = 1.17–1.86, P = 8.80 × 10-4) and PACG (OR = 1.91, 95%CI = 1.03–3.51, P = 3.88 × 10-2). Conclusion: The results of MR analysis suggested a causal relationship between AS and glaucoma. Further studies are needed to identify the specific mechanism between these two diseases.